Molecular characterization of Borrelia burgdorferi sensu lato strains isolated in the area of Belgrade, Serbia - Ristanovic,Elizabeta S. (2007)
This is the first report of the molecular characterization and identification of Borrelia burgdorferi sensu lato strains isolated in Serbia. Isolates A1, A2 and M1, from Ixodes ricinus, belong to Borrelia burgdorferi sensu stricto, while isolate K1 from Apodemus flavicollis is a mixture of Borrelia afzelii and B. burgdorferi s.s.